2020
DOI: 10.3390/md18030136
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Low-Molecular-Weight Fucoidan on Radiation-Induced Fibrosis Through TGF-β1/Smad Pathway-Mediated Inhibition of Collagen I Accumulation

Abstract: Radiation-induced fibrosis (RIF) occurs after radiation therapy in normal tissues due to excessive production and deposition of extracellular matrix proteins and collagen, possibly resulting in organ function impairment. This study investigates the effects of low-molecular-weight fucoidan (LMF) on irradiated NIH3T3 cells. Specifically, we quantified cellular metabolic activity, fibrosis-related mRNA expression, transforming growth factor beta-1 (TGF-β1), and collagen-1 protein expression, and fibroblast contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…A recent study by Wang et al stated that fucoidans inhibited TGF-β1-related epithelial-mesenchymal transition through ERK pathway in lung [137]. Wu et al [138] obtained the same data in radiation-induced fibrosis.…”
Section: Fucoidansmentioning
confidence: 79%
“…A recent study by Wang et al stated that fucoidans inhibited TGF-β1-related epithelial-mesenchymal transition through ERK pathway in lung [137]. Wu et al [138] obtained the same data in radiation-induced fibrosis.…”
Section: Fucoidansmentioning
confidence: 79%
“…The inhibition of collagen I accumulation of Oligo-Fucoidan’s radioprotection was mediated through TGF-beta1/Smad pathway [ 81 ]. Using whole genomic microarray to screen the genes are down- or upregulated by irradiation and reversed by Oligo-Fucoidan pretreatment before irradiation is highly related to the clinical setting, and we identified genes are involved in radiation and reduced by Oligo-Fucoidan pretreatment proving the efficacy of Oligo-Fucoidan on radioprotection.…”
Section: Discussionmentioning
confidence: 99%
“…Fucoidan is complex sulfated polysaccharide derived from brown seaweed, usually high molecular weight. In this study, the fucoidan was further hydrolyzed with a glycolytic enzyme to low molecular weight with average 1200 Da, 34 and contains 234.48 ± 0.08 μmol/g fucose and 49.14 ± 0.07 μmol/g galactose 32 . High molecular weight fucoidan can bind to C‐type lectin‐like receptor 2 (CLEC‐2), induce receptor clustering and platelet activation via tyrosine kinase‐dependent pathway 27 .…”
Section: Discussionmentioning
confidence: 99%
“…The OF, manufactured by Hi‐Q Marine Biotech International Ltd. (Taipei, Taiwan), was extracted from seaweed, Laminaria japonica , with distilled water (100 g of dry seaweed/5 L) and boiled at 100°C for 30 minutes, 32 and by adding glycolytic enzyme (1 mg of enzyme/g fucoidan for 6 hours) and passed through a 30 kDa molecular weight cut‐off membrane to obtain the low molecular weight fucoidan in a range between 500 and 1500 Da 33 . The same material has been used in different experiments including in vitro and in vivo models, and demonstrated that OF exhibits hepatocyte protection and anti‐radiation induced fibrosis and secondary tumor 30,31,34 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation